The fiscal crisis as a crisis in trust - Michael Haliassos (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
Neither Northerners are willing to invest in a South they perceive as unwilling to undertake necessary structural reforms, nor are Southerners willing to invest in their countries in a climate of austerity and policy uncertainty imposed, in their view, by the North. This results in a vicious cycle of mistrust. However, as the author argues, big steps in the direction of reforms may provide just enough thrust to break out of this vicious cycle, propel southern countries - and especially Greece - to a much happier future, and promote the chances for more balanced economic performance in North and South.
urn:nbn:de:hebis:30:3-340998
Keywords: 330; fiscal crisis; household liquidity; economic reforms; Greece